2006
DOI: 10.1371/journal.pctr.0010027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Inactivity on the Oxidation of Saturated and Monounsaturated Dietary Fatty Acids: Results of a Randomized Trial

Abstract: Objectives:Changes in the way dietary fat is metabolized can be considered causative in obesity. The role of sedentary behavior in this defect has not been determined. We hypothesized that physical inactivity partitions dietary fats toward storage and that a resistance exercise training program mitigates storage.Design:We used bed rest, with randomization to resistance training, as a model of physical inactivity.Setting:The trial took place at the Space Clinic (Toulouse, France).Participants:A total of 18 heal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
65
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 41 publications
8
65
0
Order By: Relevance
“…Nineteen training sessions of 35 min were programmed every 3 days, as previously described (9,15). Aerobic training was performed three to four times per week (29 sessions of 50 Ϯ 2 min total) on a vertical treadmill in a lower-body negative-pressure chamber, with intensities varying from 40 to 80% pre-bed rest maximal oxygen uptake, as previously described (15)(16)(17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen training sessions of 35 min were programmed every 3 days, as previously described (9,15). Aerobic training was performed three to four times per week (29 sessions of 50 Ϯ 2 min total) on a vertical treadmill in a lower-body negative-pressure chamber, with intensities varying from 40 to 80% pre-bed rest maximal oxygen uptake, as previously described (15)(16)(17).…”
Section: Methodsmentioning
confidence: 99%
“…Using strict bed rest as a model, we showed that physical inactivity, per se (i.e., independent of the known physical inactivity-induced energy balance changes), lowers fasting and postprandial fat oxidation (9). Unexpectedly, whereas monounsaturated dietary fat (oleate) oxidation remained unaffected by bed rest, saturated fat (palmitate) oxidation decreased by 11% (9). These results are interesting when considering the north/south gradient in obesity prevalence in France that was not associated with the overall energy intake but in the greater amount of saturated fat in the diet (10).…”
mentioning
confidence: 98%
“…In this analysis, we used a [1-13 C]acetate recovery factor in ambulatory conditions and after acute heavy-intensity exercise (85% of V O2 peak) consisting of three bouts of 10 -12 min with 10-min rest periods between bouts from seven women. Bergouignan et al (1), WISE, and LIPOX were longitudinal studies aimed at determining the effect of chronic physical activity interventions on dietary lipid oxidation. Briefly, Bergouignan et al (1) and WISE were long-term bed rests of 3 mo in 15 men and of 2 mo in 16 women, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Bergouignan et al (1), WISE, and LIPOX were longitudinal studies aimed at determining the effect of chronic physical activity interventions on dietary lipid oxidation. Briefly, Bergouignan et al (1) and WISE were long-term bed rests of 3 mo in 15 men and of 2 mo in 16 women, respectively. Both were performed at the Institute of Space Medicine and Physiology in Toulouse, France, and supported by the Centre National d'Etudes Spatiales (France), the European Space Agency, the Canadian Space Agency, and NASA.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that the acceptability and quality of the products from Iberian pig are mainly attributed to differences in the fatty acid composition of adipose tissue. On the other hand, some experiments have reported a positive effect of exercise on human health due to that exercise may play an important role in several aspects of lipid metabolism such as lipolityc activity, oxidation, and elongation and desaturation of fatty acids (Petridou et al, 2005;Votruba et al, 2005;Bergouignan et al, 2006). To our knowledge there is not enough information on the possible effect of exercise on fatty acid composition of adipose tissue from Iberian pig reared indoor and fed mixed diets.…”
Section: Introductionmentioning
confidence: 97%